2022
DOI: 10.24018/ejedu.2022.3.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer Tutoring on Pre-Service Teachers’ Physics Performance in Colleges of Education, Ghana

Abstract: At Atebubu College of Education, the study attempted to determine the impacts of peer tutoring on gender and senior High school background courses of pre-service teachers in physics. To achieve the purpose of the study an action research design was used and a total number of 140 (78 males and 62 females) who are offering primary Education program were purposively selected. The major research tools were accomplishment tests, which were used to collect quantitative data from pre-service teachers. Using the indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…It also creates more opportunities for students to practice specific skills, which leads to better retention. This agrees with the findings of (Kalu-Uche, & Ogbonna, 2020; Mkpanang, 2016;and Osei-Himah, Parker, & Naah, 2022). They all reported that the students taught using peer tutoring achieved better results than those exposed to using the lecture method.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It also creates more opportunities for students to practice specific skills, which leads to better retention. This agrees with the findings of (Kalu-Uche, & Ogbonna, 2020; Mkpanang, 2016;and Osei-Himah, Parker, & Naah, 2022). They all reported that the students taught using peer tutoring achieved better results than those exposed to using the lecture method.…”
Section: Resultssupporting
confidence: 90%
“…The teacher-centered method entails teachers acting as guardians at all times thereby reducing the students to be the lazy receiver of knowledge and consequently restricting the knowledge Open Access: https://ejournal.unma.ac.id/index.php/educatio sources of the students. In an attempt to involve students actively in the teaching-learning process, many researchers such as (Kalu-Uche, & Ogbonna, 2020;Mkpanang, 2016;and Osei-Himah, Parker, & Naah, 2022) have advocated the adoption of Class-wide Peer Tutoring (CWPT). They all reported that the students taught using peer tutoring achieved better results than those exposed to using the lecture method.…”
Section: Introductionmentioning
confidence: 99%
“…The resources reinforce the comprehension of complex scientific concepts (Ogunode et al, 2022). Mboto et al (2011) andAsare et al (2018) highlight the impact of the much-needed improvised resources in African countries such as Kenya and Ghana respectively. They report a similar circumstance to those experienced in South Africa such as the lack of instructional materials for teaching and learning in science and its effectiveness on academic achievement, therefore making the study contextually appropriate.…”
Section: Meaning Of Improvisationmentioning
confidence: 90%
“…Resources could improve students' performance and participation in class (Mboto et al, 2011;Rivera & Sanchez, 2020). It can also improve the creative skills of students (Mayeem et al, 2018), as well as sustain the interests of learners (Osei-himah et al, 2018). Given this, experimental studies have been conducted by researchers to determine the effectiveness of improvised instructional materials in science teaching and learning.…”
Section: Improvisation In Science Teaching and Learningmentioning
confidence: 99%